2005
DOI: 10.1111/j.1600-6143.2005.00866.x
|View full text |Cite
|
Sign up to set email alerts
|

A Trial of Valganciclovir Prophylaxis for Cytomegalovirus Prevention in Lung Transplant Recipients

Abstract: Cytomegalovirus (CMV) infection is common after lung transplantation. We performed a prospective trial of valganciclovir prophylaxis in lung recipients

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
67
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 24 publications
6
67
0
1
Order By: Relevance
“…Second, although all patients in our study received intravenous ganciclovir prophylaxis, CMV prophylaxis has continued to evolve and now often includes longer prophylactic periods. Although there is no standard of care regarding CMV prophylaxis among lung transplantation centers, reports of longer CMV prophylactic periods (up to 6 mo) have resulted in rates of CMV-P similar to those in this report (11,19). These data would indicate that longer course ganciclovir prophylaxis delays, but does not ultimately prevent, CMV disease.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Second, although all patients in our study received intravenous ganciclovir prophylaxis, CMV prophylaxis has continued to evolve and now often includes longer prophylactic periods. Although there is no standard of care regarding CMV prophylaxis among lung transplantation centers, reports of longer CMV prophylactic periods (up to 6 mo) have resulted in rates of CMV-P similar to those in this report (11,19). These data would indicate that longer course ganciclovir prophylaxis delays, but does not ultimately prevent, CMV disease.…”
Section: Discussionsupporting
confidence: 64%
“…This ''late-onset CMV disease,'' often defined as disease after the prophylactic period ends, has been associated with increased risk for graft failure after kidney transplantation and increased mortality in liver transplant recipients despite adequate treatment for CMV disease once detected (8,9). Several retrospective reports have also suggested that late-onset disease occurs frequently in lung recipients despite courses of prophylaxis as long as 3-6 months (10,11).…”
mentioning
confidence: 99%
“…Some other sequence variants, such as V466M (3) and T659I (35), were reported as a change from a pretreatment sequence after therapy. T659I was classified as a GCV resistance marker without specific phenotypic data (16,20,33). The findings in Table 1 add to several other UL97 sequence variants that did not confer GCV resistance after BAC mutagenesis (27).…”
Section: Discussionmentioning
confidence: 85%
“…e optimal duration of CMV prophylaxis is unknown, but in general, the longer the duration of prophylaxis, the lower the incidence of primary or recurrent CMV disease. is has been demonstrated in kidney transplant recipients aer six months of CMV prophylaxis with valganciclovir [19], and in recent studies by Humar and Zamora et al [20,21], it has been demonstrated that a longer duration of prophylaxis is bene�cial. However, it is not clear how much exposure to ganciclovir is required for effective prophylaxis.…”
Section: Discussionmentioning
confidence: 99%